SEQUENCING AND COMPARATIVE ANALYSIS OF THE MITOCHONDRIAL CYTOCHROME B GENE IN THE MARION UPLANDS FLORIDA SAND SKINK (PLESTIODON REYNOLDSI) - Locklear, Taylor R. (East Carolina University, 2016)
The Florida sand skink (Plestiodon reynoldsi)—a small (~10 cm) lizard endemic to the peninsula—is a ‘sand-swimming’ specialist restricted to Florida scrub habitat on the state’s central highland ridges. Florida scrub has been severely fragmented through urban growth and citrus farming, and less than 10% of this ecosystem remains. Given the skink’s limited geographic range and extensive population fragmentation, P. reynoldsi was listed as a federally threatened species in 1987. I surveyed skink populations from the Marion Uplands, where suitable lizard habitat is naturally (and has been historically) isolated from scrub on nearby Mt. Dora and Lake Wales ridges. I wanted to determine genetic relatedness of Marion Uplands skinks to those inhabiting these two ridges and hypothesized that Marion populations should be more similar genetically to those on the Mt. Dora ridge, given their geographic proximity. Mitochondrial DNA sequence analysis confirmed this hypothesis but also revealed unexpectedly high levels of genetic divergence between the Marion and Mt. Dora populations. Indeed, observed genetic divergence was comparable to that detected between Marion and Lake Wales populations.
Keywords: Genetics, Florida, Conservation